The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1042/bj2990041
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular localization of a protein-tyrosine phosphatase: evidence for association with chromatin

Abstract: A non-transmembrane protein-tyrosine phosphatase, PTP-S, has been shown to bind to DNA in vitro through its C-terminal noncatalytic domain. The cellular PTP-S gene product was identified as 42-44 kDa polypeptides in the rat fibroblast cell lines Rat2 and F111, by immunoblotting using polyclonal and monoclonal antibodies. Indirect immunofluorescence-staining experiments showed that PTP-S was predominantly associated with the nuclear compartment in interphase cells, although some fluorescence was present in cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 35 publications
1
31
0
Order By: Relevance
“…5 c) while relatively weak staining is seen in the nuclear matrix preparations (Fig. 5 D) indicating that majority of PTP-S is extracted along with chromatin as suggested previously [22]. The subnuclear localization was also confirmed by staining whole cells with anti-Lyn serum and observing different optical sections using a confocal microscope.…”
Section: Resultsmentioning
confidence: 60%
See 3 more Smart Citations
“…5 c) while relatively weak staining is seen in the nuclear matrix preparations (Fig. 5 D) indicating that majority of PTP-S is extracted along with chromatin as suggested previously [22]. The subnuclear localization was also confirmed by staining whole cells with anti-Lyn serum and observing different optical sections using a confocal microscope.…”
Section: Resultsmentioning
confidence: 60%
“…Previously, we have found that PTP-S, a non-transmembrane PTP, is associated with chromatin and, to a lesser extent, with the nuclear matrix [22]. Nuclear matrix preparations from HeLa and Rat 2 cells showed PTP activity using '2P-labelled poly(Glu80, Tyr20) as substrate ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous data provided evidence that a tyrosine phosphatase activity associates with the activated Met receptor (Villa-Moruzzi et al, 1993). More recently, we described the interaction of Met with PTP-S (Villa-Moruzzi et al, 1998) a soluble phosphatase located in the cytoplasm and in the nucleus of a variety of cells (Radha et al, 1994). PTP-S interacts with the juxtamembrane domain of the Met and has been implicated in regulation of cell proliferation (Kamatkar et al, 1996).…”
mentioning
confidence: 99%